Research on the Influence of Composite Modification Design on Tooth Surface Wear of Transmission Gears - Bai Xiaoning; Li Yonghua; Wang Denglong; Zhang Dongxu (Jixie chuandong)
To reduce the wear of gear tooth surface and improve its transmission performance, a composite modification design method is proposed, which is based on the Sine-SSA-BP model and used to verify the influence of modification on gear wear. According to the Archard wear model, tooth wear is calculated. The threshold and the permissible gear wear are used as the criteria to reconfigure and modify the gear tooth. The new tooth surface coordinate equations are derived respectively. Moreover, the sparrow search algorithm (SSA) improved by the Sine chaotic mapping is used to optimize the back propagation (BP) neural network, and the accuracy of Sine-SSA-BP is verified by comparing it with the traditional BP, so as to characterize the implicit relationship between the modification parameters and the gear wear. The distribution law of gear wear under the influence of modification parameters is further investigated. Finally, the optimal modification parameters are obtained through the iterative solution, and the composite modification design is carried out. The influence of modification design on the gear wear is compared and analyzed. The results show that the contact state of the tooth is significantly improved, and the gear wear is significantly reduced after the composite modification design. This method is conducive to reducing the early wear failure probability of gears and can provide theoretical reference for the anti-wear design and parameter optimization of gears.